Phylogenomic analysis of 20S proteasome gene family reveals stress-responsive patterns in rapeseed (Brassica napus L.) - Kumar, Vivek; Sharma, Hemant; Saini, Lalita; Tyagi, Archasvi; Jain, Pooja; Singh, Yogita; Balyan, Priyanka; Kumar, Sachin; Jan, Sofora; Mir, Reyazul Rouf; Djalovic, Ivica; Singh, Krishna Pal; et al. (Frontiers in Plant Science, 2022)
The core particle represents the catalytic portions of the 26S proteasomal complex. The genes encoding α- and β-subunits play a crucial role in protecting plants against various environmental stresses by controlling the quality of newly produced proteins. The 20S proteasome gene family has already been reported in model plants such as Arabidopsis and rice; however, they have not been studied in oilseed crops such as rapeseed (Brassica napus L.). In the present study, we identified 20S proteasome genes for α- (PA) and β-subunits (PB) in B. napus through systematically performed gene structure analysis, chromosomal location, conserved motif, phylogenetic relationship, and expression patterns. A total of 82 genes, comprising 35 BnPA and 47 BnPB of the 20S proteasome, were revealed in the B. napus genome. These genes were distributed on all 20 chromosomes of B. napus and most of these genes were duplicated on homoeologous chromosomes. The BnPA (α1-7) and BnPB (β1-7) genes were phylogenetically placed into seven clades. The pattern of expression of all the BnPA and BnPB genes was also studied using RNA-seq datasets under biotic and abiotic stress conditions. Out of 82 BnPA/PB genes, three exhibited high expression under abiotic stresses, whereas two genes were overexpressed in response to biotic stresses at both the seedling and flowering stages. Moreover, an additional eighteen genes were expressed under normal conditions. Overall, the current findings developed our understanding of the organization of the 20S proteasome genes in B. napus, and provided specific BnPA/PB genes for further functional research in response to abiotic and biotic stresses.